Parties and directories, ways of political sociableness in Boyacá 1930 - 1953. Construction of nation stages (2011)
The directories and political parties turned into a way of electoral signiicant joint that transformed the social and political relationships to call to electors of diverse social origin for taking part in the electoral assemblies. The parties had permanence in the time, while the directories were reinforcing their nets in preelectoral periods, in this way the political system was stirred into action in the political system of Boyacá, which was not foreign to other regions of the country.The parties and political directories were the fundamental base of the political system, which theoretically was trying to be a pluralist regime, to guarantee the free expression of the citizen and to favor the intervention of the population in the public stages. It should develop as leader in the organizational sphere, like follower in the bureaucratic stage, like an elector or maybe as antagonistic. Hereby, the directories and political parties turned into spaces of electoral joint giving importance that the population was assuming the sense of the participation, of the representation and of politics. These become into central political sociability stages which were motivating the population for assuming a political position.